Persistence of Plant-Available Phosphorus in Muck Soils after Fertilizer Application - Alan L. Wright; Edward A. Hanlon; J. Mabry McCray; David D. Sui (EDIS, 2009)
SL-290, a 5-page fact sheet by Alan L. Wright, Edward A. Hanlon, J. Mabry McCray, and David D. Sui, provides growers in the Everglades Agricultural Area with information about the organic soils in southern Florida and their management to improve crop production while also reducing adverse environmental effects, especially during times of land use change. Includes Additional sources of information. Published by the UF Department of Soil and Water Science, May 2009.